Soil-site suitability for Indian mustard in Jamnagar district of Gujarat - ST Shirgire; SG Savalia; PR Nanaware (Journal of Oilseed Brassica, 2026)
Nine typical pedons of soils of Jamnagar district in Saurashtra region, Gujarat were evaluated for theirsuitability to Indian mustard [Brassica juncea (L.) Czern & Coss.] cultivation limitations i.e. number andintensity of limitations. The study suggests that Indian mustard is moderately suitable in soils of Pedon P4, P5and P9 but marginally suitable in soils of Pedon P1, P2, P6 and P7. However, the soils of Pedon P3 and P8seems to be not suitable for Indian mustard cultivation. Soil depth, drainage, topography, and sodicity are themajor limitations for crop growth in most of the soils of Jamnagar district. Results showed that the soilsuitability classes can be improved if the correctable limitations (soil depth and drainage characteristics) arealtered through soil amelioration measures.